The Alchemist's illusion - Pandian, Gigi, 1975- (Pandian, Gigi, 1975- Accidental alchemist, 2019)
In an effort to rescue her mentor, Nicolas Flamel, centuries-old alchemist Zoe Faust and her best friend, Dorian the gargoyle chef, delve into the world of art forgery to unearth a clue hidden in a stolen painting.